Blockchain in maritime transportation: electronic bill of lading - Petronilho, Francisco Xavier Santos (2022)
The shipping industry is widely regarded as a slow adapting industry, for any innovation to be made there needs to be a real demand. One of these innovations is the electronic Bill of Lading, the need for an alternative to the expensive and slow traditional Bill of Lading has been rising since the beginning of the century. Now the digital revolution naturally introduced the electronic Bill of Lading, but its unclear legal status and different regulations in different countries make it hard to establish a worldwide solution. This work aims to provide information about the most relevant providers of electronic bills of lading focusing on the underlying technology in order to make a grounded analysis about each solution individually and in general. Some of the challenges encountered by the electronic Bill of Lading are the lack of trust and investment in innovative technologies, such as blockchain. But, it also shows promising aspects such as increased resiliency and security along with a much faster issuance and transfer for lower direct and indirect costs. At the end of this dissertation, we developed an electronic Bill of Lading solution taking into account the analysis of current solutions. This solution allows users to interact in the lifecycle of the Bill of Lading from the moment of its inception using a web application connected to the underlying blockchain that registers any interaction with the documents.